Invoice currency: Puzzling evidence and new questions from Brazil - Daniel Gersten Reiss (EconomiA, 2015)
This article for the first time uses Brazilian trade data to draw conclusions about the invoice currency choice — both in general and as it pertains to the Brazilian real (BRL). We find that the Brazil-Argentina policy of providing payment orders associated to an exchange transaction between their currencies has had a significant impact on the currency chosen for invoicing, establishing a link between the availability of financial instruments and the invoice currency choice. Moreover, the evidence does not confirm some previous international results. We identify that in Brazil there is no coincidence regarding the use of BRL for invoicing and its use for making payments. Yet we find that the main exports denominated in BRL are homogenous goods — sugar and tobacco — suggesting that some bargaining power might remain even if goods are traded in international markets. From the BRL-specific perspective, we categorically move away from the idea that the BRL is not used in Brazilian international trade. Although it is used at a limited absolute volume, an exceptional ninefold growth between 2007 and 2011 is observed. New intriguing questions about Brazilian currency usage can therefore be proposed. Este artigo utiliza pela primeira vez dados do comércio exterior brasileiro para obter conclus\~oes sobre a escolha da moeda usada para o faturamento-conclus\~oes gerais e especificas sobre o real (BRL). Nós constatamos que a política brasileiro-argentina de prover ordens de pagamento associadas a operaç\~oes de câmbio entre suas moedas teve um impacto significativo sobre a moeda escolhida para o faturamento, estabelecendo uma ligaç\~ao entre a disponibilidade de instrumentos financeiros e a escolha da moeda. Além disso, as evidências n\~ao confirmam alguns resultados internacionais anteriormente constatados. Nós identificamos que, no Brasil, n\~ao há coincidência entre a moeda utilizada para faturar e para efetuar pagamentos. Ademais, observamos que as principais exportaç\~oes faturadas em BRL s\~ao de produtos homogêneos (açúcar e tabaco), sugerindo que reste algum poder de barganha ainda que os produtos sejam comercializados em mercados internacionais. A partir da perspectiva do BRL, nós definitivamente nos afastamos da ideia de que o BRL n\~ao é utilizado no comércio exterior brasileiro. Ainda que seu uso seja limitado em valores absolutos, um crescimento de nove vezes é observado entre 2007 e 2011. A partir de agora, novas intrigantes quest\~oes sobre o uso da moeda brasileira podem ser formuladas.
Keywords: 330; British classical political economy; Genealogy of power; Liberal art of government; Biopolitics